The State of food and agriculture 2005 : : agricultural trade and poverty : can trade work for the poor?.. - Food and Agriculture Organization of the United Nations; Food and Agriculture Organization of the United Nations (Rome: Food and Agriculture Organization of the United Nations, 2005)
Can trade work for the poor? Trade and trade liberalization affect the poor and food-insecure. Trade can be a catalyst for change, promoting conditions that enable the poor to raise their incomes and live longer, healthier and more productive lives. But because the poor often survive on a narrow margin, they are particularly vulnerable in any reform process, especially in the short run as productive sectors and labor markets adjust. Opening national agricultural markets to international competition - especially from subsidized competitors - before basic market institutions and infrastructure are in place can undermine the agriculture sector with long-term negative consequences for poverty and food security. Among the many important lessons from this analysis is the need for policy-makers to consider carefully how trade and complementary policies can be used to promote pro-poor growth. The report recommends a twin-track approach: investing in human capital, institutions and infrastructure to enable the poor to take advantage of trade-related opportunities, while establishing safety nets to protect vulnerable members of society.
Podnaslov na ovojnici: Agricultural trade and poverty : can trade work for the poor?
Keywords: Food supply -- -- Developing countries; Agriculture -- -- Developing countries; Free trade -- -- Developing countries; Poor -- -- Developing countries; kmetijstvo -- revščina -- statistika -- države v razvoju